Enantioseparation of (±)-trans-β-lactam ureas by supercritical fluid chromatography - Jurin, Mladenka; Kontrec, Darko; Dražić, Tonko; Roje, Marin (Croatica chemica acta, 2020)
In this study the enantioseparation of (±)-trans-β-lactam ureas 1a-g by supercritical fluid chromatography (SFC) was examined using different polysaccharide based chiral stationary phases (CSPs), and CO2/alcohol (70:30, V/V) as the mobile phase. The...
Im Titel sind "+" und "-" untereinander geschrieben: "+" hochgestellt, "-" tiefgestellt
Published online: May 12, 2021
Gesehen am 16.03.2022